PENGEMBANGAN EKONOMI KREATIF DESA MELALUI BADA USAHA MILIK DESA (BUMDES) MENUJU KOPERASI BERBASIS IT - Wibowo, Hendro (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2021)
The allocation of Village Funds (Dana Desa) from year to year increased, the Central Government has allocated Village Funds in 2015 amounting to Rp 20 trillion and in 2016 increased to Rp 47 trillion and in 2017 increased to Rp 60 trillion. For the province of Banten in 2015 has received village funds amounting to Rp 200 billion, in 2016 increased to Rp 791 billion and in 2017 to Rp 1 trillion. With the Village Fund is required accountability of village financial management in terms of planning, implementation, administration, reporting, accountability, guidance and supervision of village finances and to know the accountability of village financial management. The future goal of the allocation of Village Funds from the Central Government in order to form a Village Owned Enterprise (Badan Usaha Milik Desa). This study aims to develop the allocation of Village Funds can be allocated in the manufacture of Village Owned Enterprises with legal status of Koperasi by developing the potential of existing Village Economics based on Technology using Financial System Technologi and Market Place. Keywords: Alokasi Dana Desa (ADD), BUMDes, Fintech dan Market Place